The evaluation of strength imbalances as risk factor for contactless injuries of the knee and thigh: a critical review - Möck, S.; Happ, K.; Wirth, K. (The Journal of Sports Medicine and Physical Fitness, 2023)
Contact injuries are difficult to prevent in sports because of the influence of many uncontrollable factors. Non-contact injuries, on the other hand, appear to be controllable and therefore predictable due to their exclusively internal nature. Nevertheless, the scientific community is still searching in vain for indicators to reliably predict the likelihood of injuries to athletes in order to prevent them. Therefore, a critical review of published data was conducted to discuss the current evaluation of strength imbalances as risk factors for contactless knee and thigh injuries. Different approaches to measure muscle strength, detect asymmetries, and methodological issues with the final goal of evaluating their relationship with injury rates was considered as well. All common strength tests on the basis of which an injury risk assessment is calculated had high to excellent ICC values. However, we found that all these tests have their respective limitations and problems. The HQ Ratio can be determined using different contraction forms or calculation methods. This variance in procedures in use makes uniform interpretation enormously difficult. Regardless, we found moderate or strong evidence of no association with future hamstring injury for half of all variables. For lateral differences, we were unable to find any relevant data directly indicating an influence on injury probability. Thus, to date, no significant relationship between asymmetries and non-contact injuries has been detected for either inter- or intra-limb differences. Therefore, the assessment of strength imbalances can only be considered as one component in a multifactorial approach to assess potential injury risks.